The Second Paycheck to Keep Up With the Joneses: Relative Income Concerns and Labor Market Decisions of Married Women - Yongjin Park (University of Massachusetts, Department of Economics, 2005)
This paper investigates whether ones effort to keep up with the Joneses has any effect on labor supply behavior. We provide a simple model and empirical evidence that labor supply decisions of married women are influenced by relative as well as absolute income of their husbands. We find, after controlling for husbands absolute income and other individual characteristics, that married women are more likely to be in labor force when their husbands relative income is low. Results are robust across various settings and measures of relative income and the size of the effect is economically meaningful. We also show that income inequality of reference group of husbands in age-regional cross sections can be a predictor of their wives labor supply.
Keywords: H23; D31; D62; J22; 330; Interdependent utility; relative income; social comparisons; inequality; emulation; labor market participation of married women